2014
DOI: 10.1007/s00261-014-0199-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric MRI findings of transitional zone prostate cancers: correlation with 3-dimensional transperineal mapping biopsy

Abstract: Preliminary study indicates MR findings which can help differentiate a BPH nodule from transitional zone prostate cancers which could help direct biopsy in the large and growing number of people suspected of having prostate cancer. Further work will be needed for validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…In PI-RADS v2.1, however, the DWI score has gained more importance and scores of 4 and 5 can now upgrade the overall score of a TZ lesion [4]. This adjustment is consistent with studies demonstrating lower ADC values in TZ cancers than in BPH nodules, albeit with a large overlap of ADC values [26,[28][29][30], and studies showing higher diagnostic accuracy when T2WI-and DWI assessments were combined in TZ lesions [11,31]. The presented data shows another potential of DWI findings: the terms "restricted diffusion," "diffusion-weighted hyperintensity," and "ADC hypointense" had high NPVs of 89.4% to 91.8% for TZ lesions, whereas T2WI-related terms showed lower NPVs with a maximum of 66.0% for TZ lesions.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In PI-RADS v2.1, however, the DWI score has gained more importance and scores of 4 and 5 can now upgrade the overall score of a TZ lesion [4]. This adjustment is consistent with studies demonstrating lower ADC values in TZ cancers than in BPH nodules, albeit with a large overlap of ADC values [26,[28][29][30], and studies showing higher diagnostic accuracy when T2WI-and DWI assessments were combined in TZ lesions [11,31]. The presented data shows another potential of DWI findings: the terms "restricted diffusion," "diffusion-weighted hyperintensity," and "ADC hypointense" had high NPVs of 89.4% to 91.8% for TZ lesions, whereas T2WI-related terms showed lower NPVs with a maximum of 66.0% for TZ lesions.…”
Section: Discussionsupporting
confidence: 72%
“…In TZ lesions, the descriptors "water-dropshaped," "irregular," "non-circumscribed," and "erased charcoal sign" also showed high PPVs between 50.0 and 78.6%. In a previous study with 14 included patients, Pokharel et al [11] found a similar PPV for TZ lesions with an irregular border (55%). The term "organized chaos" showed a favorable PPV of 5.4% indicating benignity in TZ lesions.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, it is believed that rFOV reduces the partial volume effect between tumors and normal tissue and that it reflects a more accurate ADC values [12,13,18]. Despite these differences, the mean ADC values of prostate cancer in our study were within the range of measurements in previous reports [6,13,24].…”
Section: Discussioncontrasting
confidence: 54%
“…5,8,9 Through multiparametric magnetic resonance imaging (mp-MRI) (combining T 2 -weighted [T 2 W] MRI with functional imaging, mainly diffusion-weighted imaging [DWI]) detection and diagnosis of APC has improved considerably. Multiple studies have demonstrated that mp-MRI has high accuracy for detection of APC 1,[10][11][12][13][14][15][16][17][18] and with the use of imageguided biopsy techniques that combine data from mp-MRI to TRUS or in-bore MRI guidance systems for targeting of lesions, a diagnosis of APC can now be readily established in clinical practice. 7,[19][20][21][22] Despite increased awareness and improved ability to diagnose APC, staging of anterior tumors remains problematic.…”
mentioning
confidence: 99%